Exploring the experience of mainland Chinese undergraduate students at an American university - Wu, Wei (Kansas State University, 2013)
Previous studies of the experiences of mainland Chinese students in the U.S. have focused on graduate students, the most prolific Chinese demographic change before 2008. However, a significant increase in mainland Chinese undergraduate students has occurred in American universities since 2008, and these students have different features from Chinese graduate students. Meanwhile, research on the mainland Chinese undergraduate student experience was very limited. For example, what are the sources of stress of these Chinese undergraduate students? What were their coping strategies? What changes did they have in the process? How do they evaluate their experience in the U.S.? This study is an attempt to answer these questions. This study employed a qualitative research method and a case study research design to examine the experience of six mainland Chinese undergraduate students in a midwestern American public university. Convenience, snowball and criterion sampling were used to identify the participants, who were conducted a semi-structured interview with in-depth follow-up probing sessions to yield data. Berry’s (1997) acculturation framework was the theoretical framework for the study. Patterns that emerged from the data include: (1) six stressors are discovered in participants’ acculturation process: language barrier, cultural difference, life skills-related stressors, relationships with others, academic studies, and concern for the future (including job opportunity and pressure for marriages). The stressors vary based on individual factors and their length of time in the U.S; (2) participants used three coping strategies to cope with stressful situation: problem focused, emotions focused and avoidance-orientation strategies; participants mainly rely on friends or roommates to cope with problems and are not aware of university’s resources for help; (3) participants experienced many changes in this process, including improved English skill, independence, stress management, changed perceptions about U.S. and China; (4) participants’ overall evaluation of the experience is positive but they don’t think studying in the U.S. is for everyone; they hope university to provide more help overcome the difficulties; (5) participants also talked about dissatisfaction about Chinese education, cheating problems at the American university, using agents when applying for universities, desire to return to China eventually and their family financial support. Themes emerged crossing all patterns included: (1) participants did not what to expect before they went abroad but managed to overcome difficulties in the U.S.; (2) participants are willing to make changes and improve themselves by overcoming all barriers with the resources they know; (3) participants desire more help from the university to overcome the barriers to a better education; (4) participants seek better job opportunities whether in China or in the U.S. soon after graduation, but they eventually will go back China; (5) participants’ family fully support participants’ endeavor to study in the U.S. As a conclusion, the study makes recommendations to American university administrators, professors and Chinese students who plan to come to the U.S. American universities should develop a holistic approach to help Chinese international students. Language and cultural training and engagement is important. Partnership programs between American students and Chinese students may be established to help them with language and cultural training. At the same time, life-skills, relationship skills, academic study skills and training are needed for students who came during high school or after high school. The university should also use standardized test for admission to ensure quality of students. Professional career help is a very critical need for these students in China and in America. Finally, the study recommends further research to better understand this unique population.
Keywords: Educational leadership; International education; Chinese undergraduate students; Higher Education Administration (0446)